A production method of a 2507 stainless steel pump casting - XIAN HONGJUN; LIU CONGJIANG (2018)
The invention relates to a production method of a 2507 stainless steel pump casting. The method includes (1) die designing and manufacturing, (2) moulding and core manufacturing, (3) paint brushing, (4) sand mould and sand core drying, (5) mould assembling, (6) smelting, (7) pouring, (8) mould disassembling and sand removing, (9) gate and riser removing, (10) repair welding, and (11) polishing andshot blasting. Through a reasonable casting process design, casting defects including air holes, oxide slag inclusion and cracks are prevented, the repair rate and the rejection rate of casting are reduced, product quality is ensured, subsequent repair welding is greatly reduced, and the production cost of the casting is reduced. 本发明涉及种2507不锈钢泵铸件的生产方法，该方法包括以下步骤：(1)模具设计、制作；(2)造型和制芯；(3)刷涂料；(4)砂型、砂芯哄干；(5)合箱；(6)熔炼；(7)浇注；(8)开箱、清砂；(9)去除浇冒口；(10)补焊；(11)打磨、抛丸。本发明通过合理的铸造工艺设计，防止了气孔、氧化夹渣及裂纹的铸造缺陷，降低了铸件的返修率和废品率，保证了产品质量，后续补焊量也大为减少，降低了铸件的生产成本。